Diseño del proceso industrial para la producción de inmunoglobulina a partir del lactosuero - Carrera Vizuete, Carlos Daniel (2022)
In Ecuador, the use of whey in dairy companies is currently a latent problem, as it has been considered to affect the constitutional rights of living in a healthy environment and food security, a situation that is due to the fact that the country does not have processing plants for the dairy by-product. The present research project aims to develop sustainable industrial alternatives for the recovery and use of this discarded product. In the province of Cotopaxi, there are 134 dairy microenterprises with artisanal technology. These small companies make inappropriate use of the whey, which is used for animal feed and dumped into rivers, sewers and soil, causing major environmental problems. The methodology used for the development of the research is: the search for updated information on the existing types of whey, the analysis of its composition, the analysis of the methods that facilitate the separation of the proteins present in this by-product and its purification. The types of research used for the development of the project are explanatory and qualitative, and the methods used are inductive-deductive and analysis and synthesis. Based on this information, the design of the industrial process for obtaining immunoglobulin is proposed with the description of each of its stages and control parameters. As a conclusion of the work, it has been considered that membrane technologies are the most efficient to separate and concentrate whey proteins, the electrophoresis method for their separation, in this case to isolate immunoglobulin.